Classic and backdoor pathways of androgen biosynthesis in human sexual development - Hyun Gyung Lee; Chan Jong Kim (Korean Society of Pediatric Endocrinology, 2022)
Both genes and hormones regulate human sexual development. Although ovarian hormones are not essential for female external genitalia development, male sexual development requires the action of testicular testosterone and dihydrotestosterone (DHT). DHT is the most active endogenous androgen formed by the conversion of testosterone in genital skin. This synthesis route from cholesterol to DHT is called the conventional classic pathway. Recent investigations have reported an alternative ("backdoor") route for DHT formation that bypasses fetal testicular testosterone. This alternative route plays a crucial role in human hyperandrogenic disorders like congenital adrenal hyperplasia caused by P450c21 deficiency, polycystic ovary syndrome, and P450 oxidoreductase deficiency. In addition, mutations in AKR1C2 and AKR1C4, genes encoding 3α-reductases, have been implicated in disorders of sexual development, indicating that both the classic and backdoor routes are required for normal human male sexual development. More recently, androsterone was found to be the primary androgen of the human backdoor route. Androsterone and steroidal substrates specific to the backdoor route are predominantly found in the placenta, liver, and adrenal glands rather than in the testes. These findings are essential to understanding human sexual development.